Anaphora, Cataphora, and Exophora Found in The Jakarta Post Published in March 2021 - Varia Virdania Virdaus; Saiful Rifa'i (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
Pronouns are words that are used to refer to another word in a text, particularly in newspapers. It can become an issue if students do not grasp how to use a pronoun to refer to a single item in a text since most students focus solely on the meaning of each pronoun that they are familiar with, ignoring the meaning of context from the text. As a result, this research examines the types of pronouns and references that are commonly employed in newspapers. This study employed descriptive quantitative because it analyzes, describes, and counts the three types of references: Anaphora, Cataphora, and Exophora, according to the Jakarta Post's business news from March 2021. There were 31 news sources in this analysis. Anaphora is the most commonly used in this publication, according to the results of the analysis. Cataphora is the second series, and Exophora is the last. As a result, this research can help people better understand the context of a text when pronouns are used as a reference.